Christian Ethics as Witness Barth's Ethics for a World at Risk. - Haddorff, David (Havertown : James Clarke & Co, 2011)
Christian ethics is less a system of principles, rules, or even virtues, and more of a free and open-ended responsible witness to God's gracious action to be with and for others and the world. Postmodernity has left us with the risky uncertainty of knowing and doing the good. It also leaves us with the global risks of political violence and terrorism, economic globalization and financial crisis, and environmental destruction and global climate change. How should Christians respond to these problems? Haddorf creatively explores how Christian ethics is best understood as a witness to God's actio.
Chapter eight Witness and the PowersChapter nine Witness and Public Ethics: Options in Christian Ethics; Part four Christian Ethics as Witness; Chapter ten Witness and Christian Responsibility; Chapter eleven Political Witness: For Faith and Peace; Chapter twelve Economic Witness: For Love and Justice; Chapter thirteen Environmental Witness: For Hope and Freedom; Bibliography; Back Cover.
Print version record.
Master record variable field(s) change: 072
Keywords: Barth, Karl, -- 1886-1968.; Barth, Karl, -- 1886-1968.; Christian ethics; Barth, Karl, 1886-1968.; Christian ethics; RELIGION -- Christian Theology -- Ethics; Christian ethics; RELIGION / Christian Theology / Ethics; Electronic books